Assessment of the accuracy of digital surgical planning and its implementation with tibial plateau levelling osteotomy - Henry Todd; Jack Fawsitt; Nicholas Goody; Darren James Shaw; Dylan Neil Clements (Veterinary Research Communications, 2026)
Introduction Pre-operative planning of orthopaedic procedures is widely regarded as critical to their safe execution; however, the ability to both accurately plan and enact the plan have not been assessed in the veterinary context. The aim of this study was to assess the ability of boarded surgeons compared to surgical trainees to reproducibly plan a TPLO and then to implement this plan in vivo and in vitro . Methods Twelve participants planned 10 TPLOs from blinded radiographs of dogs diagnosed with cranial cruciate ligament disease; this was repeated four weeks later and compared between surgical groups using linear mixed-effect models (LME). To assess the ability of a participant to implement their pre-operative planning in vivo , pre-operative TPLO plans were compared to post-operative radiographs for each patient using LME in 6 participants. In vitro , three 3D printed tibial models were provided to 8 surgeons. Each participant was asked to perform a TPLO osteotomy to predefined measurements and accuracy of this osteotomy was compared between groups using LME Results Neither the accuracy of pre-operative planning, nor the ability to accurately implement the plan at surgery, consistently changed with surgeon experience. Using 3D printed models, surgical trainees differed significantly from predetermined D1 ( p = 0.019), D2 ( p = 0.002) values and carried out significantly distomedial to proximolateral angled osteotomies ( p < 0.001). However, surgical trainees and board-certified surgeons were not significantly different from each other when assessing the accuracy of in vitro osteotomies. Conclusion Pre-operative planning is accurate across differing experience levels and is a valuable tool for the safe execution of canine TPLOs. Accuracy of implementation of the plan during surgery is similar between groups, but surgical trainees were less accurate than residency trained surgeons when undertaking TPLO osteotomies on tibial models. This highlights the critical requirement for intra-operative supervision of surgical trainees.